C-reactive Protein Level in Bangladeshi Preeclamptic Patients and Its Comparison with Trimester-Matched Normal Pregnancy (Medicine Today, 2023)
Introduction with objective: Preeclampsia is a major cause of maternal and fetal morbidity and mortality in Bangladesh. This study aimed to estimate C-reactive protein (CRP) level among patients with preeclampsia and to compare with those of trimester-matched normal pregnancy.Materials and Methods: : This cross-sectional study was done from January 2005 to December 2006 at the different tertiary care hospital at Dhaka. A total of 33 preeclamptic and 33 normal pregnant women in the third trimester were enrolled in the study. The PE patients were divided into two groups: mild hypertension [diastolic blood pressure (DBP) =1gm/l) and group II (3+_3gm/l). Both PE and control groups were matched for their age and parity. Estimation of serum CRP was done by Turbulometry method.Results: CRP concentration (mg/l) was 4.55±2.83 in control group and 23.52±24.85 in PE group which was significantly higher than in control group. CRP level was significantly higher (p